ЛЕКСИКА ВИНОГРАДАРСТВА НА ФРАНЦУЗСКОМ И УЗБЕКСКОМ ЯЗЫКАХ ЛИНГВОКУЛЬТУРОЛОГИЧЕСКИЙ АНАЛИЗ И НАУЧНЫЕ ВЗГЛЯДЫ УЧЕНЫХ - Radjabov, Ruslan (Центр Научных Публикаций (buxdu.uz), 2022)
This article is based on scientific research in the field of viticulture, in particular, research on grape varieties and terminology grown in Uzbekistan and France. It aims to create glossaries and glossaries in the field based on the scientific opinions and experiences of scientists